Skate Arena Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionisme - Rabsanjani, Azali; Aldy, Pedia; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Skateboarding, BMX, and Inline Skating are kind of extreme sports, these sports entered indonesia in the 70-80s. The rapid development of this extreme sport in Pekanbaru cannot be denied by emergence of the community of each of these extreme sports, but the rapid development of this sports is not accompanied by adequate facilities. These athletes of extreme sports players often practice in outdoor such as city park, Main Stadium Riau, Kaharudin Nasution Stadium, and in the Arena Loop. The lack of facilities is an obstacle for these athletes and extreme sports players for more develop talent and many times several International and National Event can not do in Pekanbaru, because of inadequate facilities. Therefore to solve this problem is needed Skate Arena located in Pekanbaru to facilitate all the needs of this extreme sport, and become a container for national and international events. Based on the extreme nature owned by this sport, and the similarity of how to play is to play by passing obstacle while showing tricks, then the concept of designing Skate Arena is to pass the obstacle. The concept will be applied through the principle of Architecture Expressionism. The extreme natura of the sport will be translated through the use of red materials, the nature of the obstacle will be translated trough the use of wood materials, and concrete which is a charateristic of obstacle material, and provides a ramp that penetrates.Keywords: Extreme sports, Skateboard, BMX, Inline Skate, Architecture Expressionism